THERMAL RESISTANCE OF POLYETHYLENE TEREPHTHALATE FIBRES: THERMAL RESISTANCE OF POLYETHYLENE TEREPHTHALATE FIBRES - Velev, Valentin; Popov, Anton; Veleva, Lyubomira; Todorov, Nikola (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The thermal resistance of isotropic and orientated poly(ethylene terephthalate) (PET) samples was studied. Part of the oriented PET specimens was heat mechanically modified under different conditions. Using differential thermal analysis (DTA), thermal gravimetric analysis (TGA) and differential thermal gravimetric analysis (DTGA) it was investigated the influence of the forming methods and the modes of heat mechanically treatment on the relative samples thermal oxidation stability. It was determined basic thermodynamic and kinetic parameters, as well as the limiting mechanisms of the basic destruction of the PET objects.